Combination of Technology Blockchain and Multiversion Concurrency Control for Developing Database with Peer-to-Peer Atomic Safe Transactions - A. Ivanova, I.; D. Kotilevets, I.; S. Karbova, E.; A. Pavelyev, S. (International Journal of Engineering and Technology, 2018)
The article discusses the mechanisms of consensus algorithms used in a blockchain without connection with crypto-currencies, compares with the functionality of competitive access control technology to the database, and combines the functions of blockcahin and MultiVersion Concurrency Control in databases to obtain peer-to-peer atomic safe transactions of strictly defined "facts", written down in an irrefutable audit journal.Â Â